اللغة الإنكليزية لغير الناطقين بها : ثقافة وطنية ام اجنبية - أ. م. د. ويس جلود ابراهيم (University of Mosul-college of Basic Education, 2005)
Plenty of differences can be found in the cultures of different nations. The realization of a linguistic expression demands knowing what the expression means for the native speaker. To gain a growing comprehension of cultural meanings one has to undertake wide readings where words are met in a variety of contexts. The importance of culture is emphasized for language learning. Culture includes all the social practices that bond a group of people together and distinguish them from others. It is the accepted and patterned ways of behaviour of a given people. It includes ways of thinking, feeling, acting and doing things in certain ways. The aim of the work is to study the relationship between language and culture. The study attempts to incorporate culture into classroom by means of considering some techniques. What is said or accepted in a particular situation may not be said or accepted in a similar situation in a different culture. The stages of learning cultural context are identified. Differences in cultural meanings and semantic changes are also discussed. The ideal setting for teaching a language is the country where it is spoken. The teaching of culture should be an integral part of the foreign language instruction. A knowledge of behaviour of other people is important if the student is to communicate fully in the target language. Without the study of foreign culture, foreign language instruction is inaccurate and incomplete. Finally, the research provided some conclusions and recommendations for students and language teachers.